2023
DOI: 10.1101/2023.03.25.23287718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential viral introductions and spread of BA.1 drove the Omicron wave across Pakistani provinces

Abstract: Background: COVID-19 waves caused by specific SARS-CoV-2 variants have occurred globally at different times. We focused on Omicron variants to understand the genomic diversity and phylogenetic relatedness of SARS-CoV-2 strains in various regions of Pakistan. Methods: We studied 276,525 COVID-19 cases and 1,041 genomes sequenced from December 2021 to August 2022. Sequences were analyzed and visualized using phylogenetic trees. Results: The highest case numbers and deaths were recorded in Sindh and Punjab, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Multifarious studies have characterised the initial introduction of SARS-CoV-2 to specific regions (Gonzalez-Reiche et al 2020;Dı ´ez-Fuertes et al 2020;Deng et al 2020;Gámbaro et al 2020;Bedford et al 2020;Moreno et al 2020;Maurano et al 2020;Paiva et al 2020;Komissarov et al 2021;Muenchhoff et al 2021;da Silva Filipe et al 2021;Lobiuc et al 2021;Murall et al 2021;Juscamayta-López et al 2021;Githinji et al 2021;du Plessis et al 2021;Tordoff et al 2021;Mallon et al 2021;Lemieux et al 2021;McBroome et al 2022;Borges et al 2022), or variants of SARS-CoV-2 to regions (Stefanelli et al 2020;Tang et al 2021;Toovey et al 2021;Alpert et al 2021;Elliott et al 2022;Michaelsen et al 2022;Fonager et al 2022;Nasir et al 2022;Bukhari et al 2023). A previous phylogenetic analysis of 225 Irish genomes from two pandemic waves suggested that multiple introductions of SARS-CoV-2 to Ireland from outside had taken place (Mallon et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Multifarious studies have characterised the initial introduction of SARS-CoV-2 to specific regions (Gonzalez-Reiche et al 2020;Dı ´ez-Fuertes et al 2020;Deng et al 2020;Gámbaro et al 2020;Bedford et al 2020;Moreno et al 2020;Maurano et al 2020;Paiva et al 2020;Komissarov et al 2021;Muenchhoff et al 2021;da Silva Filipe et al 2021;Lobiuc et al 2021;Murall et al 2021;Juscamayta-López et al 2021;Githinji et al 2021;du Plessis et al 2021;Tordoff et al 2021;Mallon et al 2021;Lemieux et al 2021;McBroome et al 2022;Borges et al 2022), or variants of SARS-CoV-2 to regions (Stefanelli et al 2020;Tang et al 2021;Toovey et al 2021;Alpert et al 2021;Elliott et al 2022;Michaelsen et al 2022;Fonager et al 2022;Nasir et al 2022;Bukhari et al 2023). A previous phylogenetic analysis of 225 Irish genomes from two pandemic waves suggested that multiple introductions of SARS-CoV-2 to Ireland from outside had taken place (Mallon et al 2021).…”
Section: Introductionmentioning
confidence: 99%